Uporaba metod strojnega učenja za preučevanje odnosov med značilnostmi branik in okoljem - Jevšenak, Jernej (Acta silvae et ligni, 2017)
Many studies have shown that by using nonlinear methods, the relationship between tree-ring parameters and the environment can be described (modelled) better and in more detail. In our study, (multiple) linear regression (MLR) with four nonlinear machine learning methods are compared: artificial neural networks (ANN), model trees (MT), bagging of model trees (BMT) and random forests of regression trees (RF). To compare the different regression methods, four datasets were used. The performance of the learned models was estimated by using 10-fold cross-validation and an additional hold-out test. For all datasets, better results were obtained by the nonlinear machine learning regression methods, which can explain more variance and yield lower error. However, none of the considered methods outperformed all other methods for all datasets. Therefore, we suggest testing several different methods before selecting the best one, e.g. for climate reconstruction.
Keywords: strojno učenje; primerjava metod; dendroklimatologija; umetne nevronske mreže; modelna drevesa; naključni gozdovi; linearna regresija